Investment Policy of a Region in the Conditions of the Budgetary Restrictions and Economic Sanctions - Avramenko, Elena Semyonovna; Vlasov, Semyon Vasilyevich; Lukyanov, Sergey Aleksandrovich; Temkina, Irina Mikhaylovna (Economy of Regions, 2015)
The article is devoted to the assessment of influence of budgetary restrictions and economic sanctions on investment policy of a region. The paper studies the bilateral negative effect on socio-economic development of regions from both the external sanctions and braking mechanism of economic development within the country. On the basis of the comparative and statistical analysis, the need to change focus of investment policy from the growth in volumes to qualitative perfecting is proved. The new direction of investment policy connected with the import substitution process realization, its combination with acceleration of innovative development on the certain example of Sverdlovsk region is analyzed. The conclusions and offers stated in the article are applicable to the public authorities of subjects of the Russian Federation, experts in the sphere of regional investment policy and improvement of investment climate, and also the specialized organizations specialized in attracting investment and work with investors in regions of Russia.